Biostimulatory effect of low-level laser therapy on keratinocytes in vitro - Basso, Fernanda G.; Oliveira, Camila F. [UNESP]; Kurachi, Cristina; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (Springer Nature, 2013)
Epithelial cells play an important role in reparative events. Therefore, therapies that can stimulate the proliferation and metabolism of these cells could accelerate the healing process. To evaluate the effects of low-level laser therapy (LLLT), human keratinocytes were irradiated with an InGaAsP diode laser prototype (LASERTable; 780 ± 3 nm; 40 mW) using 0.5, 1.5, 3, 5, and 7 J/cm2 energy doses. Irradiations were done every 24 h totaling three applications. Evaluation of cell metabolism (MTT assay) showed that LLLT with all energy doses promoted an increase of cell metabolism, being more effective for 0.5, 1.5, and 3 J/cm2. The highest cell counts (Trypan blue assay) were observed with 0.5, 3, and 5 J/cm2. No statistically significant difference for total protein (TP) production was observed and cell morphology analysis by scanning electron microscopy revealed that LLLT did not promote morphological alterations on the keratinocytes. Real-time polymerase chain reaction (qPCR) revealed that LLLT also promoted an increase of type I collagen (Col-I) and vascular endothelial growth factor (VEGF) gene expression, especially for 1.5 J/cm2, but no change on fibroblast growth factor-2 (FGF-2) expression was observed. LLLT at energy doses ranging from 0.5 to 3 J/cm2 promoted the most significant biostimulatory effects on cultured keratinocytes. © 2012 Springer-Verlag London Ltd.
Keywords: Epithelial cells; Gene expression; Low-level laser therapy; cell protein; collagen type 1; fibroblast growth factor 2; vasculotropin; cell count; cell metabolism; cell stimulation; cell structure; cell transformation; controlled study; diode laser; gene expression; human; human cell; in vitro study; irradiation; keratinocyte; low level laser therapy; metabolic rate; priority journal; protein expression; protein synthesis; radiation dose; type I collagen gene; vascular endothelial growth factor gene